The role of BLS import and export price indexes in the real GDP. (Monthly Labor Review, 2015)
The article discusses the use of import and export indexes from the U.S. Bureau of Labor Statistics (BLS) International Price Program (IPP) in calculating the real gross domestic product (GDP). Topics include the role of the BLS in the creation of economic measure, the foreign component of GDP, and the importance of import and export price indexes to government policymakers and private business.